2017
DOI: 10.17576/jsm-2017-4611-17
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Fractal Dimension on Capillary Pressure Curve to Evaluate the Tight Sandstone

Abstract: The rock of gas tight reservoir is more heterogeneous than that of conventional sandstone reservoir and is more prone to water-blockage because of the invasion of operation fluid. This paper presented a new approach for the analysis of the capillary pressure curve for tight gas reservoir. Herein, the saturation equation with fractal dimension proved the previous observation that the log-log plot of capillary pressure against water saturation is a straight line, which is quite different from the popular observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…The existing studies show that fractal dimensions determined by the NMR T 2 spectrum and capillary pressure curve are considered as constants or segmental constants. When there are several types of pores with different geometries in the rock system, the fractal dimension of segments must be used to accurately describe the changes of pore geometry. Assuming that the change rule of pore geometry is related to the pore size, then, the change rule of the fractal dimension is related to the pore size, and then, the pore structure of the rock meets the variable dimension fractal theory.…”
Section: Variable Dimension Fractal-based Convention Methods Between ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The existing studies show that fractal dimensions determined by the NMR T 2 spectrum and capillary pressure curve are considered as constants or segmental constants. When there are several types of pores with different geometries in the rock system, the fractal dimension of segments must be used to accurately describe the changes of pore geometry. Assuming that the change rule of pore geometry is related to the pore size, then, the change rule of the fractal dimension is related to the pore size, and then, the pore structure of the rock meets the variable dimension fractal theory.…”
Section: Variable Dimension Fractal-based Convention Methods Between ...mentioning
confidence: 99%
“…In the existing studies, fractal dimensions determined by the NMR T 2 spectrum and capillary pressure curve are considered as constants or segmental constants. However, the constant and segmental constant fractal dimension cannot accurately reflect the pore geometry difference between large pores and small pores. Hence, it is necessary to study a fractal-based conversion method with a pore structure that considers a fractal dimension coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…16 Through the fractal method, Guo et al suggested a straight line in the log−log plot of capillary pressure versus water saturation. 17 and tortuosity. 18 They further examined the relationship between fractal dimensions and pore structure parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Miao et al proposed analytical models for seepage characteristics and extended the methodology to analyze the seepage characteristics of slug flow in fractal porous media . Through the fractal method, Guo et al suggested a straight line in the log–log plot of capillary pressure versus water saturation . This straight-line capillary function is quite different from the widely used Corey’s correlation.…”
Section: Introductionmentioning
confidence: 99%